BAFF Blockade Attenuates DSS-Induced Chronic Colitis via Inhibiting NLRP3 Inflammasome and NF-κB Activation - Zhang, Ying; Tao, Meihui; Chen, Chaoyue; Zhao, Xi; Feng, Qinyu; Chen, Guang; Fu, Yu (Frontiers in Immunology, 2022)
BAFF production is increased in IBD patients. However, the specific role of BAFF in IBD is still uncovered. This study aimed to investigate the expression and function of BAFF in experimental colitis as well as the potential mechanisms.BAFF levels in the serum, colon tissues and source were measured in DSS-induced colitis mice. Mouse-derived BAFF antibody was administered in DSS mice. The changes of body weight, disease activity index (DAI) scores, colon length, spleen weight, histopathological damage, inflammatory indicators, NF-κB signaling and NLRP3 inflammasome were assayed in DSS mice and control. LPS-primed RAW264.7 cells and bone marrow derived macrophages (BMDMs) were treated with BAFF blockage and recombinant mouse BAFF. Inflammatory associated cytokines, NLRP3 inflammasomes and NF-κB signaling were detected among groups. BAFF production was elevated systemically and locally in colitis mice. BAFF blockade improved the body weight loss, DAI scores, colon length, spleen weight and histopathological damage in colitis mice. Immunoflurescence analysis revealed that elevated macrophages in mucosal lamina propria was the primary sourse of BAFF in the colon. NLRP3 inflammasome and NF-κB signaling pathway activation were dramatically inhibited in DSS mice treatmented with BAFF blockage. In LPS-primed RAW264.7 cells / BMDMs, BAFF blockade decreased the activation of NLRP3 inflammasome (NLPR3, ASC, cleaved IL-1β, IL-18, cleaved caspase 1) via inhibiting NF-κB signaling pathway. Moreover, LPS synergizes with BAFF to promote inflammatory factor secretion and expression of NF-κB signaling pathway in RAW264.7 cells. These results suggested that BAFF blockade protected against colitis partially by relieving inflammation, inhibiting intestinal NLRP3 inflammasome and NF-κB signaling pathway from macrophages. BAFF plays an important role in inflammation regulation in IBD, thus providing a novel idea for further research on colitis and experimental evidences for novel potential therapeutic target in IBD.